2014
DOI: 10.1021/ma5019044
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Poly(3-hexylthiophene)s via Lithium–Bromine Exchange

Abstract: Poly(3-hexylthiophene) (P3HT) is one of the most extensively investigated conjugated polymers and has been employed as the active material in many devices including field-effect transistors, organic photovoltaics and sensors. As a result, methods to further tune the properties of P3HT are desirable for specific applications. Herein, we report a facile postpolymerization modification strategy to functionalize the 4-position of commercially available P3HT in two simple steps–bromination of the 4-position of P3HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Fully or partially brominated P3HT ( Fig. 1(a)) was synthesized according to a literature procedure, 14 in which partially brominated P3HT was prepared by changing the ratio of N-bromosuccinimide (NBS) toward P3HT (the ratio of NBS toward P3HT was 1% (…”
Section: Synthesis Of Pristine P3ht Fully and Partially Brominated Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Fully or partially brominated P3HT ( Fig. 1(a)) was synthesized according to a literature procedure, 14 in which partially brominated P3HT was prepared by changing the ratio of N-bromosuccinimide (NBS) toward P3HT (the ratio of NBS toward P3HT was 1% (…”
Section: Synthesis Of Pristine P3ht Fully and Partially Brominated Pmentioning
confidence: 99%
“…It has been suggested that bromination of P3HT disturbs the delocalization of p-conjugated electrons on the P3HT backbone. [12][13][14] In this study, we examined the effects of inter-and intra-chain delocalization of p-electrons in a P3HT on the device performances, using P3HT brominated to varying degrees. The relationship between the degree of delocalization of p-electrons along the P3HT backbone and the photovoltaic properties of the resulting Br-P3HT:PCBM BHJ solar cells is discussed semiquantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the material properties can be also tuned via modification the π‐conjugated backbone that has great impact on the electronic structure, such as ionization potential, electron affinity, and electronic delocalization . In recent years, different strategies have been developed to a fine‐tuning energy level through the careful combinations of different subunits or the incorporation of electron‐donating/electron‐withdrawing substituents into backbones . For example, fluorine atom has been widely incorporated into polymer backbones that significantly influence the energy level, backbone planarity, solubility, and crystallization .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] In recenty ears, different strategies have been developed to af ine-tuning energy level through the careful combinationsofdifferent subunits or the incorporation of electron-donating/electron-withdrawings ubstituents into backbones. [23][24][25][26][27] For example, fluorine atom has been widely incorporated into polymer backbones that significantly influence the energy level, backbonep lanarity,s olubility,a nd crystallization. [28][29][30][31] Indeed, this fluorination strategy is known to be valuable for tuning the properties of the photovoltaic materials, as successfully demonstrated by the increase of the open circuit voltage via lowering of the highest occupied molecularo rbital (HOMO) of the materiala nd suppressingc harge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, thiophene‐based organic polymers have recently attracted significant attentions in both academia and industrial applications of electronic and optical technologies , and their laterally pending boronic acid‐containing derivatives have been confirmed that they find usage in a range of technology from biosensors to biomedical applications . More recently, a theoretical description of the photo induced electron transfer in these systems were given as between the separate donor and acceptor moieties , and as a result organoborane polymers were being studied for use in organic light emitting devices, such as optical, electronic, and sensor applications .…”
Section: Introductionmentioning
confidence: 99%